(untitled) (Ideal Journal of Multidisciplinary Research, 2026)
This article analyzes the strategic importance of the serve in modern table tennis and the technique of limiting opponent’s reaction and seizing game initiative. The study examines serve performance indicators of highly qualified athletes, highlighting technical, tactical, and psychological aspects of effective serve execution. Results indicate that the serve is the most crucial technical element directly influencing match outcomes. The article describes analytical and contextual methods of serve development, as well as strategies for disorienting opponents and exploiting their weaknesses.